Hungarian Monitoring, 29 May 1990 . [Magyar rádiófigyelő], 1990. május 29 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Berlin is to operate a single and unified Parliament - About the railway strike in Poland - Yeltsin is the President of the Russian Federation Domestic Affairs: - About exiting the Warsaw Pact - American delegation at the plenary session of the Parliament - Hungarian Finance Minister in talks in Paris - Initiatives for the modifying the Constitution - The Constitutional Court to decide on the death penalty - Prisoners' riots Külpolitika: - Berlin az egységes parlament működését tervezi - A lengyel vasutassztrájkról - Jelcin az Orosz Föderáció elnöke Belpolitika: - A Varsói Szerződésből való kilépésről - Amerikai küldöttség a parlament plenáris ülésén - Párizsban tárgyal a magyar pénzügyminiszter - Alkotmánymódosítási javaslatok - Alkotmánybíróság előtt a halálbüntetés kérdése - Börtönlázadások